Autoidentificación y preferencia racial en niños de educación primaria urbano y rural del sur peruano - Arévalo Quijano, José Carlos (2024)
The research aimed to understand how self-identification dynamics and racial preferences manifest in primary school children from urban and rural areas of southern Peru and to discern the underlying causes of discrimination and racism in these contexts. Methodologically, the research was based on a qualitative approach under a naturalistic paradigm, using case studies. The sample included 24 students from urban and rural educational institutions in the southern highlands of Peru, distributed across three departments: Apurímac, Ayacucho, and Huancavelica. The Doll Test questionnaire, inspired by the original Doll Test from the 1940s, was used to investigate children’s perceptions and attitudes toward race. The results revealed the presence of racial stereotypes and prejudices in students’ perceptions and preferences regarding skin color. The study highlights the need to promote a culture of inclusion and respect from early childhood and underscores the importance of implementing educational and cultural interventions to eradicate these stereotypes. The research aligns and contrasts with previous studies in other contexts, suggesting that racial perceptions are influenced by both local cultural and global factors.